2016
DOI: 10.1111/his.12909
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of forkhead box M1 (FoxM1) expression and antitumour effect of FoxM1 inhibition in melanoma

Abstract: We have shown the prognostic impact of FoxM1 on melanoma patients. FoxM1 inhibition may be a potential therapeutic option for advanced melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…Overexpression of the pleiotropic transcription factor FOXM1 has been observed in many human malignancies and regulates multiple pathways important for tumorigenesis (5,6). Recent studies demonstrate FOXM1 overexpression in malignant melanoma and an association with cancer stage and prognosis suggesting FOXM1 knockdown may be a novel therapeutic target (7)(8)(9). Consistent with these studies, we observed reduction in FOXM1 at micromolar Siomycin A doses in the metastatic melanoma cell line, SK-MEL-28, with a rather rapid drop-off in FOXM1 expression at concentrations above 1 µM.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Overexpression of the pleiotropic transcription factor FOXM1 has been observed in many human malignancies and regulates multiple pathways important for tumorigenesis (5,6). Recent studies demonstrate FOXM1 overexpression in malignant melanoma and an association with cancer stage and prognosis suggesting FOXM1 knockdown may be a novel therapeutic target (7)(8)(9). Consistent with these studies, we observed reduction in FOXM1 at micromolar Siomycin A doses in the metastatic melanoma cell line, SK-MEL-28, with a rather rapid drop-off in FOXM1 expression at concentrations above 1 µM.…”
Section: Discussionsupporting
confidence: 90%
“…FOXM1 expression has been noted to be constitutively activated in many cancers including melanoma and to contribute to tumorigenesis and chemo-and radio-resistance (5,(7)(8)(9). A series of 10 melanoma cell lines were tested for FOXM1 protein expression by Western blotting with two different FOXM1 antibodies.…”
Section: Constitutive Foxm1 Expression In Melanoma Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…GO analysis of the RNA-seq revealed enrichment in pathways involved in cell division and proliferation (Figure S3C), consistent with the phenotypic effects of AMIGO2 knockdown. Interestingly, RPPA analysis did not show significant and/or consistent changes in components of the MAPK signaling pathway (Figure S3D), but did reveal significant changes in FOXM1 (Figures S3B and S3E; Table S3), a TF implicated in melanoma proliferation by promoting cell-cycle progression (Bhat et al, 2008; Ito et al, 2016; Miyashita et al, 2015). Thus, our profiling data suggest that AMIGO2 loss results in transcriptional changes affecting proliferation prior to cell death.…”
Section: Resultsmentioning
confidence: 99%
“…All formalin-fixed (24 h in 10% buffered formalin) and paraffin-embedded (i.e., formalin-fixed paraffin-embedded (FFPE)) tissues were obtained from our hospital's archives. IHC staining was performed as reported previously [16][17][18][19][20]. Briefly, the archival FFPE tissue blocks were cut into 4-µm-thick tissue sections and then deparaffinized and rehydrated.…”
Section: Immunohistochemistrymentioning
confidence: 99%